Membrane-type 1 matrix metalloproteinase cytoplasmic tail-binding protein-1 is a new member of the Cupin superfamily. A possible multifunctional protein acting as an invasion suppressor down-regulated in tumors. - Uekita, T; Gotoh, I; Kinoshita, T; Itoh, Y; Sato, H; Shiomi, T; Okada, Y; Seiki, M (2004)
Membrane-type 1 matrix metalloproteinase (MT1-MMP/MMP-14) is an enzyme that promotes tumor cell invasion in tissues. Although the proteolytic activity of MT1-MMP is indispensable for invasion, it is also regulated by functions of the cytoplasmic tail. In this study we obtained a new human gene whose product binds to the tail sequence in yeast. The product, MTCBP-1, is a 19-kDa protein that belongs to the newly proposed Cupin superfamily composed of proteins with diverse functions. MTCBP-1 expressed in cells formed a complex with MT1-MMP and co-localized at the membrane. It was also detected in both the cytoplasm and nucleus, where MT1-MMP does not exist. In human tumor cell lines MTCBP-1 expression was significantly low compared with non-transformed fibroblasts, and enforced expression of MTCBP-1 inhibited the activity of MT1-MMP in promoting cell migration and invasion. MTCBP-1 showed significant homology to the bacterial aci-reductone dioxygenase, which is an enzyme in methionine metabolism. The C-terminal part of MTCBP-1 is identical to Sip-L, which is reported to be important for human hepatitis C virus replication. Thus, MTCBP-1 may have multiple functions other than the regulation of MT1-MMP, which presumably depends on the subcellular compartment.